Aircraft fairing surface conductive coating and preparation method thereof
By using conductive phthalonitrile and a stepped temperature curing process, a graphite-like microcrystalline network and a triazine ring cross-linked network were constructed, which solved the problems of poor conductivity, radar signal transparency, and environmental adaptability of the conductive coating of the aircraft fairing, and achieved the stability and long-term service performance of the coating.
Patent Information
- Application Number
- CN202511458619.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2025-12-23
AI Technical Summary
Existing conductive coatings for aircraft fairings struggle to balance conductivity and radar signal transmittance, and are prone to structural defects and performance degradation in high and low temperature and corrosive environments.
Using conductive phthalonitrile as the core material, a graphite-like microcrystalline network and a triazine ring cross-linked network are formed through molecular structure design and a stepped temperature curing process. Combined with 3-aminopropyltriethoxysilane coupling agent, a dense coating is constructed to achieve conductivity that is compatible with radar signals.
It achieves a balance between conductivity and radar signal transparency, and the coating remains stable in high and low temperature and corrosive environments, making it suitable for long-term service in aerospace.
Smart Images

Figure CN121182253A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive coating technology, and in particular to a conductive coating for the surface of an aircraft fairing and its preparation method. Background Technology
[0002] As a key component of aerospace equipment, the aircraft fairing must simultaneously achieve four core functions: aerodynamic optimization, static electricity dissipation, radar transparency, and environmental tolerance. It must rapidly dissipate static electricity generated by air friction during flight to prevent discharge interference with radar signals or potential safety hazards; it must match the dielectric properties of air and the substrate to reduce radar signal reflection and attenuation; and it must withstand extreme environmental corrosion such as high-altitude high-low temperature cycles, high-speed airflow erosion, and salt spray corrosion. However, existing fairing conductive coating technologies still face significant bottlenecks in balancing multiple performance aspects and engineering practicality. Existing conductive coatings mostly rely on conductive filler doping or simple conjugation modification to achieve conductivity, but it is difficult to achieve a balance of performance. In filler doping systems, high addition amounts of carbon nanotubes, metal powders, etc. are required to form conductive channels, resulting in a sharp increase in the dielectric constant of the coating and a steep dielectric gradient with air and the radome substrate, causing strong radar signal reflection. Moreover, fillers are prone to agglomeration, which not only causes uneven conductivity but also increases dielectric loss, exacerbating signal attenuation. Although simple conjugation modification systems (such as thiophene-modified resins) do not have agglomeration problems, the conjugated segments have poor stacking properties, resulting in little improvement in conductivity, which cannot meet the requirements for antistatic properties. Furthermore, the high molecular polarity makes it difficult to control dielectric loss.
[0003] Coating density is fundamental to conductivity continuity and protection, but existing processes are prone to structural defects. Most coatings employ one-step high-temperature curing, where solvents rapidly boil and evaporate while the resin has already begun cross-linking and curing, reducing fluidity and forming micropores or cracks. This disrupts conductive channels and provides pathways for corrosive media to penetrate. Some resins are excessively rigid, resulting in high curing shrinkage, further exacerbating cracking. Moreover, the coating and substrate often have weak bonds, making them prone to peeling off under high-speed airflow, completely losing their conductivity and protective functions.
[0004] Traditional coatings are ill-suited to the complex environment at high altitudes: the glass transition temperature of substrates such as epoxy resin is less than 150°C, and they are prone to softening at high temperatures, leading to the collapse of the conductive network; pure high-temperature resistant resins require filler doping, which leads to a return to performance imbalance. At the same time, metal fillers are prone to oxidation and corrosion, their conjugated chains are easily broken by ozone, and their interfaces are prone to cracking under high and low temperature cycling, resulting in a gradual decline in conductivity over the years, which cannot meet the requirements for long-term service. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and to propose a conductive coating for the surface of an aircraft fairing and its preparation method.
[0006] To achieve the above objectives, the present invention provides a conductive coating for the surface of an aircraft fairing, comprising the following raw materials in parts by weight: conductive phthalonitrile: 90-110 parts, N,N-dimethylformamide: 180-300 parts, dispersant BYK-110: 2-5 parts, 3-aminopropyltriethoxysilane: 1-3 parts, leveling agent BYK-333: 0.5-2 parts, and defoamer BYK-066N: 0.5-1 part; The preparation process of the conductive phthalonitrile includes the following steps: (1) Under nitrogen protection, 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to anhydrous dichloromethane, cooled to -78°C, and boron tribromide was added dropwise. During the dropwise addition, the temperature was controlled not to exceed -70°C. After the dropwise addition was completed, the mixture was stirred at -78°C for 1 h, and then allowed to return to room temperature naturally. The reaction was continued for 6-10 h. Then, deionized water was added to quench excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. The chemical reaction equation is as follows: ; The structure of the product was confirmed by ¹H NMR. In this reaction, boron tribromide, acting as a strong Lewis acid, preferentially forms a coordinate bond between its boron atom and the oxygen atom of the methoxy group in the substrate, generating a stable oxygen-boron complex. This complexation significantly weakens the CO bond, making the methoxy group an easily leaving group. The activated CO bond is readily converted by Br in the system. - The reaction proceeds to nucleophilic substitution, generating an aryloxyboron intermediate and methyl bromide. Upon addition of deionized water, the aryloxyboron intermediate undergoes hydrolysis, releasing 1-hydroxythiophene[3,4-c]pyrrole-4,6(5H)-dione. Boric acid byproducts are generated and can be removed by washing. (2) Under nitrogen protection, 5-bromo-2-fluoro-aniline, 4,4-dihydroxystilbene, and potassium carbonate were added to dimethyl sulfoxide. The mixture was stirred and heated to 150-170℃ for 6-10 h. After cooling to room temperature, the solid was precipitated in dilute hydrochloric acid solution, filtered, and collected. The solid was recrystallized from ethanol to obtain monomer A. The chemical reaction equation is as follows: ; The structure of the product was confirmed by 1H NMR; (3) Under nitrogen protection, monomer A, 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, potassium carbonate and potassium iodide were added to anhydrous sulfolane. The mixture was heated to 135-145℃ with stirring and reacted for 6-8 hours. After cooling to room temperature, the precipitate was poured into dilute hydrochloric acid solution, collected by filtration, washed three times with ethanol, and dried to obtain monomer B. The chemical reaction equation is as follows: ; The structure of the product was confirmed by 1H NMR; (4) Under nitrogen protection, monomer B was added to anhydrous sulfolane, and the mixture was heated to 80-90℃ with stirring. 4-nitro-2-trifluoromethyl-phthalonitrile was added, and the reaction was carried out for 8-10 hours. After cooling to room temperature, the solid was poured into dilute hydrochloric acid solution to precipitate, filtered, and the solid was collected. After washing three times with ethanol, the solid was dried to obtain conductive phthalonitrile. The chemical reaction equation is as follows: ; The structure of the product was confirmed by H NMR.
[0007] Preferably, in (1), the molar ratio of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione and boron tribromide is 1:1-1.5.
[0008] Preferably, in (1), 1-methoxythiopheno[3,4-c]pyrrole-4,6(5H)-dione and anhydrous dichloromethane are in a weight ratio of 1:8-12.
[0009] Preferably, in (1), gradient elution refers to the volume ratio of dichloromethane and methanol in the eluent of each step being 1:0, 50:1, 20:1 to 10:1.
[0010] Preferably, in (2), the molar ratio of 5-bromo-2-fluoro-aniline, 4,4-dihydroxystilbene and potassium carbonate is 2-2.4:1:2-3.
[0011] Preferably, in (2), the weight ratio of 5-bromo-2-fluoro-aniline, dimethyl sulfoxide and dilute hydrochloric acid solution is 1:8-12:20-30.
[0012] Preferably, the mass concentration of the dilute hydrochloric acid solution in (2) is 10%.
[0013] Preferably, in (3), monomer A, 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, potassium carbonate and potassium iodide are in a molar ratio of 1:1-1.5:1.5-2:0.1-0.2.
[0014] Preferably, in step (3), monomer A, anhydrous sulfolane, and dilute hydrochloric acid solution are in a weight ratio of 1:8-12:20-30.
[0015] Preferably, the mass concentration of the dilute hydrochloric acid solution in (3) is 10%.
[0016] Preferably, in (4), monomer B and 4-nitro-2-trifluoromethyl-phthalonitrile have a molar ratio of 1:2-2.4.
[0017] Preferably, in step (4), monomer B, anhydrous sulfolane, and dilute hydrochloric acid solution are in a weight ratio of 1:8-12:20-30.
[0018] Preferably, the mass concentration of the dilute hydrochloric acid solution in (4) is 10%.
[0019] Furthermore, the present invention also provides a method for preparing the conductive coating on the surface of the above-mentioned aircraft fairing, comprising the following steps: S1. Add conductive phthalonitrile to N,N-dimethylformamide and stir at room temperature for 30-60 min. Then add dispersant BYK-110, 3-aminopropyltriethoxysilane, leveling agent BYK-333, and defoamer BYK-066N. Continue stirring under ultrasonication for 10-20 min. After passing through a 200-mesh filter, the conductive coating is obtained. S2. Polish the surface of the aircraft fairing to remove dust and impurities. In a cleanroom, use a gravity spray gun to evenly spray conductive coating onto the surface of the aircraft fairing. Then, use stepped temperature rise to cure the coating and complete one application of conductive coating. Repeat this process three times to obtain a conductive coating on the surface of the aircraft fairing.
[0020] Preferably, the stepped temperature rise curing process in S2 is as follows: Phase 1: Room temperature → 120℃, heating rate 2℃ / min, hold for 1 hour; Phase 2: 120℃→200℃, heating rate 2℃ / min, hold for 1 hour; Phase 3: 200℃→500℃, heating rate 5℃ / min, hold for 2 hours.
[0021] Preferably, the working mechanism of the conductive coating on the surface of the aircraft fairing in this invention is as follows: The conductivity mechanism of Ben-Amin's conductive coating is the result of the synergistic effect of the charge transport basis of the original molecular conjugated structure and the enhanced conductivity caused by partial carbonization during curing. The core component of the coating, conductive phthalonitrile, is molecularly designed to provide a conductive basis: it uses 4,4-dihydroxystilbene as its backbone, and in the benzene ring -CH=CH- benzene ring structure, the vinylidene sp... 2The hybrid carbon forms a continuous conjugated system with the π electrons of the two benzene rings, providing a basic channel for intramolecular charge migration. The thiophene-pyrrole dione unit connected by ether bonds further expands the delocalization range of the conjugated electrons. The cyano group of the terminal phthalonitrile undergoes a trimerization reaction in the early stage of curing to form a triazine ring crosslinking network. The rigid heterocyclic structure fixes the molecular orientation and promotes the close π-π stacking of conjugated segments of adjacent molecules, building a bridge for charge transmolecular transport. When the curing temperature is increased to 500℃, the coating undergoes partial carbonization, further improving conductivity. At this temperature, the conductive phthalonitrile resin molecular chains lose some O and N heteroatoms, and the original conjugated chains further condense, gradually forming microcrystalline regions with a graphite-like structure. In the graphite layered structure, π electrons can move freely within the layers, significantly reducing charge transport resistance. Simultaneously, the triazine ring crosslinking network formed in the early stage is transformed into a more stable carbon skeleton after partial carbonization. The originally dispersed conjugated regions are connected by carbon bridges formed by carbonization, constructing a continuous conductive network across the coating. This allows charges to migrate not only along the conjugated chains of individual molecules but also to achieve long-distance, low-resistance transport through the graphite microcrystalline regions. Furthermore, the defect sites formed by some residual N and O heteroatoms in the carbon skeleton can be further optimized by adjusting the Fermi level, while the partial crosslinking structure retained during carbonization prevents the collapse of the molecular skeleton, ensuring the orderly distribution of the graphite microcrystalline regions and guaranteeing the continuity and stability of the conductive network. The coating achieves a balance between conductivity and radar signal transmission through molecular structure design and density control. In the 4-nitro-2-trifluoromethyl-phthalonitrile unit introduced at the end of the conductive phthalonitrile, the trifluoromethyl group acts as a strong electron-withdrawing group, reducing the total molecular dipole moment and suppressing the polarization effect of the coating in the applied radar signal electric field. This keeps the dielectric constant within a gradient range compatible with air and the radome substrate, significantly reducing signal reflection at the coating surface. Simultaneously, the dense coating structure constructed through step-curing and multiple spraying processes, combined with the low polarity of the molecular skeleton, maintains extremely low dielectric loss, preventing excessive attenuation of the radar signal during transmission within the coating.
[0022] The coating's environmental tolerance and performance stability stem from the dual guarantees of cross-linked network construction and process optimization. During curing, the triazine ring network formed by the phthalonitrile cyano trimer possesses high bond energy and chemical stability, endowing the coating with excellent high-temperature resistance and enabling it to resist corrosion from salt spray, ozone, and other corrosive media. The 3-aminopropyltriethoxysilane coupling agent significantly improves coating adhesion by binding to the matrix through silicon-oxygen bonds and interacting with resin molecules through amino groups, preventing peeling caused by high-speed airflow erosion or high-low temperature cyclic stress. In the stepped temperature curing process, the slow heating and heat preservation process avoids solvent boiling and the formation of micropores, while the leveling agent further optimizes the coating smoothness. Combined with three layers of spraying, a dense structure without obvious defects is formed, which not only blocks the penetration path of corrosive media but also ensures the continuity of the conductive network, achieving stable performance during long-term service.
[0023] The beneficial effects of this invention are: 1. This invention solves the core bottleneck of existing coatings, which struggle to balance conductivity and transparency, through precise molecular structure design. The conductive phthalonitrile uses 4,4-dihydroxystilbene as a conjugated backbone, combined with thiophene-pyrrole dione to expand the electron delocalization range. Partial carbonization at 500℃ forms a graphite-like microcrystalline network, constructing low-resistance conductive channels to efficiently conduct static electricity generated during flight. Simultaneously, the trifluoromethyl group in the terminal 4-nitro-2-trifluoromethyl-phthalonitrile reduces the molecular dipole moment, allowing the dielectric constant to adapt to the gradient between the air and the fairing substrate. Combined with a dense structure to control dielectric loss, this significantly reduces radar signal reflection and attenuation, perfectly meeting the dual requirements of fairing static dissipation and signal transmission.
[0024] 2. This invention overcomes the problems of existing coatings having "numerous structural defects and easy performance degradation" through process optimization and cross-linking network design. During the stepped temperature curing process, segmented heating and heat preservation allow the solvent to evaporate slowly, avoiding the formation of micropores or cracks; the three-layer spraying combined with the leveling agent ensures uniform coating thickness. The triazine ring cross-linking network formed after curing has high bond energy, possessing both high temperature resistance and corrosion resistance; 3-aminopropyltriethoxysilane strengthens the chemical bonding between the coating and the substrate, preventing peeling caused by high-speed airflow erosion or high and low temperature cycling; the dense structure and stable interface together ensure the continuity of the conductive network, achieving long-term service without performance degradation. 3. This invention optimizes performance while also addressing industrialization needs, solving the problems of complex preparation and difficulty in scale-up of existing high-end coatings. The four-step synthesis process of conductive phthalonitrile is clear and controllable, the raw materials are readily available and the reaction conditions are mild, and purification can be achieved by conventional methods such as silica gel column chromatography. The coating preparation uses N,N-dimethylformamide as a solvent, combined with commercial additives (dispersants, leveling agents, etc.), and the ultrasonic dispersion and filter filtration processes are simple and easy to implement. The stepped temperature curing and gravity spraying equipment are mature, requiring no special high-end instruments, and can be directly adapted to existing coating production lines, providing technical support for large-scale mass production.
[0025] 4. This invention provides a coating system designed for complex high-altitude environments, completely overcoming the shortcomings of traditional coatings in terms of "poor environmental adaptability." The triazine ring crosslinking network endows the coating with excellent high-temperature resistance, capable of withstanding cyclic stress from 150°C to -60°C; the carbon skeleton, after carbonization strengthening, resists salt spray corrosion and ozone erosion, preventing conjugated chain breakage or oxidation of metal fillers; simultaneously, the dense structure blocks the penetration path of corrosive media, and the coupling agent ensures stable interfacial bonding. Even after long-term high and low temperature cycling and salt spray erosion, it can still maintain stable electrical conductivity and physical integrity, meeting the requirements for long-term aerospace service. Attached Figure Description
[0026] Figure 1 The 1H NMR spectrum of 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione prepared in Example 2 of this invention; Figure 2 The H NMR spectrum of monomer A prepared in Example 2 of this invention; Figure 3 The 1H NMR spectrum of monomer B prepared in Example 2 of this invention; Figure 4 The H NMR spectrum of the conductive phthalonitrile prepared in Example 2 of this invention. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0028] Preparation Example 1: A specific preparation method for conductive phthalonitrile, including the following steps: (1) Under nitrogen protection, 100g of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to 800g of anhydrous dichloromethane, cooled to -78℃, and 136.76g of boron tribromide was added dropwise. During the dropwise addition, the temperature was controlled not to exceed -70℃. After the dropwise addition was completed, the mixture was stirred at -78℃ for 1h, and then allowed to return to room temperature naturally. The reaction was continued for 6h. Then, deionized water was added to quench the excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution (dichloromethane and methanol were eluted in volume ratios from 1:0, 50:1, 20:1 to 10:1) to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. (2) Under nitrogen protection, 100g of 5-bromo-2-fluoro-aniline, 55.85g of 4,4-dihydroxystilbene and 72.73g of potassium carbonate were added to 800g of dimethyl sulfoxide. The mixture was stirred and heated to 150℃ for 6h. After cooling to room temperature, the solid was precipitated in 2kg of 10% dilute hydrochloric acid solution. The solid was filtered, collected, and recrystallized with ethanol to obtain monomer A. (3) Under nitrogen protection, 100g of monomer A, 30.46g of 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, 37.34g of potassium carbonate and 2.99g of potassium iodide were added to 800g of anhydrous sulfolane. The mixture was heated to 135℃ with stirring and reacted for 6h. After cooling to room temperature, the mixture was poured into 2kg of 10% dilute hydrochloric acid solution to precipitate. The precipitate was collected by filtration, washed three times with ethanol, and dried to obtain monomer B. (4) Under nitrogen protection, 100g of monomer B was added to 800g of anhydrous sulfolane, and the mixture was heated to 80℃ with stirring. 66.18g of 4-nitro-2-trifluoromethyl-phthalonitrile was added, and the mixture was reacted for 8h. After cooling to room temperature, the solid was precipitated in 2kg of 10% dilute hydrochloric acid solution, filtered, collected, washed three times with ethanol, and dried to obtain conductive phthalonitrile.
[0029] Preparation Example 2: A specific preparation method for conductive phthalonitrile, including the following steps: (1) Under nitrogen protection, 100g of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to 1kg of anhydrous dichloromethane, cooled to -78℃, and 164.11g of boron tribromide was added dropwise. During the dropwise addition, the temperature was controlled not to exceed -70℃. After the dropwise addition was completed, the mixture was stirred at -78℃ for 1h, and then allowed to return to room temperature naturally. The reaction was continued for 8h. Then, deionized water was added to quench the excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution (dichloromethane and methanol were eluted in volume ratios from 1:0, 50:1, 20:1 to 10:1) to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. (2) Under nitrogen protection, 100g of 5-bromo-2-fluoro-aniline, 50.56g of 4,4-dihydroxystilbene and 82.31g of potassium carbonate were added to 1kg of dimethyl sulfoxide. The mixture was stirred and heated to 160℃ and reacted for 8h. After cooling to room temperature, the solid was precipitated in 2.5kg of 10% dilute hydrochloric acid solution. The solid was filtered, collected, and recrystallized with ethanol to obtain monomer A. (3) Under nitrogen protection, 100g of monomer A, 36.56g of 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, 45.56g of potassium carbonate and 4.48g of potassium iodide were added to 1kg of anhydrous sulfolane. The mixture was heated to 140℃ with stirring and reacted for 7h. After cooling to room temperature, the mixture was poured into 2.5kg of 10% dilute hydrochloric acid solution to precipitate. The precipitate was collected by filtration, washed three times with ethanol, and dried to obtain monomer B. (4) Under nitrogen protection, 100g of monomer B was added to 1kg of anhydrous sulfolane, and the temperature was raised to 85℃ with stirring. 72.79g of 4-nitro-2-trifluoromethyl-phthalonitrile was added, and the reaction was carried out for 9h. After cooling to room temperature, the solid was poured into 2.5kg of 10% dilute hydrochloric acid solution to precipitate. The solid was filtered, collected, washed three times with ethanol, and dried to obtain conductive phthalonitrile.
[0030] Preparation Example 3: A specific method for preparing conductive phthalonitrile, including the following steps: (1) Under nitrogen protection, 100g of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to 1.2kg of anhydrous dichloromethane, cooled to -78℃, and 205.14g of boron tribromide was added dropwise. During the dropwise addition, the temperature was controlled not to exceed -70℃. After the dropwise addition was completed, the mixture was stirred at -78℃ for 1h, and then allowed to return to room temperature naturally. The reaction was continued for 10h. Then, deionized water was added to quench the excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution (dichloromethane and methanol were eluted in volume ratios from 1:0, 50:1, 20:1 to 10:1) to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. (2) Under nitrogen protection, 100g of 5-bromo-2-fluoro-aniline, 46.35g of 4,4-dihydroxystilbene and 90.54g of potassium carbonate were added to 1.2kg of dimethyl sulfoxide. The mixture was stirred and heated to 170℃ and reacted for 10h. After cooling to room temperature, the solid was precipitated in 3kg of 10% dilute hydrochloric acid solution. The solid was filtered, collected, and recrystallized with ethanol to obtain monomer A. (3) Under nitrogen protection, 100g of monomer A, 45.69g of 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, 49.78g of potassium carbonate and 5.98g of potassium iodide were added to 1.2kg of anhydrous sulfolane. The mixture was heated to 145℃ with stirring and reacted for 8h. After cooling to room temperature, the mixture was poured into 3kg of 10% dilute hydrochloric acid solution to precipitate. The precipitate was collected by filtration, washed three times with ethanol, and dried to obtain monomer B. (4) Under nitrogen protection, 100g of monomer B was added to 1.2kg of anhydrous sulfolane, and the temperature was raised to 90℃ with stirring. 79.41g of 4-nitro-2-trifluoromethyl-phthalonitrile was added, and the reaction was carried out for 10h. After cooling to room temperature, the solid was poured into 3kg of 10% dilute hydrochloric acid solution to precipitate. The solid was filtered, collected, washed three times with ethanol, and dried to obtain conductive phthalonitrile.
[0031] Comparative Preparation Example 1: The difference between Comparative Preparation Example 1 and Preparation Example 2 is that 4,4-dihydroxystilbene is replaced with 4,4-dihydroxybiphenyl, whose chemical structure is as follows: .
[0032] Comparative Preparation Example 2: The difference between Comparative Preparation Example 2 and Preparation Example 2 is that 5-bromo-2-fluoro-aniline is not added, and in order to ensure that the reaction can proceed, 4,4-dihydroxystilbene is replaced with 4,4-dibromostilbene, whose chemical structural formula is as follows: ; The specific preparation method is as follows: The specific preparation method of conductive phthalonitrile includes the following steps: (1) Under nitrogen protection, 100g of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to 1kg of anhydrous dichloromethane, cooled to -78℃, and 164.11g of boron tribromide was added dropwise. During the dropwise addition, the temperature was controlled not to exceed -70℃. After the dropwise addition was completed, the mixture was stirred at -78℃ for 1h, and then allowed to return to room temperature naturally. The reaction was continued for 8h. Then, deionized water was added to quench the excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution (dichloromethane and methanol were eluted in volume ratios from 1:0, 50:1, 20:1 to 10:1) to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. (2) Under nitrogen protection, 100g of 4,4-dibromo-stilbene, 60.04g of 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, 71.55g of potassium carbonate and 7.37g of potassium iodide were added to 1kg of anhydrous sulfolane. The mixture was heated to 140℃ with stirring and reacted for 7h. After cooling to room temperature, the precipitate was poured into 2.5kg of 10% dilute hydrochloric acid solution. The precipitate was collected by filtration, washed three times with ethanol, and dried to obtain monomer A. (3) Under nitrogen protection, 100g of monomer A was added to 1kg of anhydrous sulfolane, and the temperature was raised to 85℃ with stirring. 103.10g of 4-nitro-2-trifluoromethyl-phthalonitrile was added, and the reaction was carried out for 9h. After cooling to room temperature, the solid was poured into 2.5kg of 10% dilute hydrochloric acid solution to precipitate, filtered, collected, washed three times with ethanol, and dried to obtain conductive phthalonitrile.
[0033] Comparative Preparation Example 3: The difference between Comparative Preparation Example 3 and Preparation 2 is that 4-nitro-2-trifluoromethyl-phthalonitrile is replaced with 4-nitro-phthalonitrile.
[0034] Example 1: A specific method for preparing a conductive coating on the surface of an aircraft fairing, comprising the following steps: S1. Add 900g of conductive phthalonitrile prepared according to Preparation Example 1 to 1.8kg of N,N-dimethylformamide, stir at room temperature for 30min, then add 20g of dispersant BYK-110, 10g of 3-aminopropyltriethoxysilane, 5g of leveling agent BYK-333, and 5g of defoamer BYK-066N, and continue stirring under ultrasonication for 10min. After passing through a 200-mesh filter, a conductive coating is obtained. S2. Polish the surface of the aircraft fairing to remove dust and impurities. In a cleanroom, use a gravity spray gun to evenly spray conductive coating onto the surface of the aircraft fairing. Then, use a stepped temperature curing method. Stage 1: room temperature → 120℃, heating rate 2℃ / min, and heat preservation for 1 hour. Phase 2: 120℃→200℃, heating rate 2℃ / min, holding for 1h; Phase 3: 200℃→500℃, heating rate 5℃ / min, holding for 2h; complete one conductive coating application, repeat three times to obtain a conductive coating on the surface of the aircraft fairing.
[0035] Example 2: A specific method for preparing a conductive coating on the surface of an aircraft fairing, comprising the following steps: S1. Add 1 kg of conductive phthalonitrile prepared according to Preparation Example 2 to 2.4 kg of N,N-dimethylformamide, stir at room temperature for 45 min, then add 35 g of dispersant BYK-110, 20 g of 3-aminopropyltriethoxysilane, 10 g of leveling agent BYK-333, and 7 g of defoamer BYK-066N, and continue stirring under ultrasonication for 15 min. After passing through a 200-mesh filter, the conductive coating is obtained. S2. Polish the surface of the aircraft fairing to remove dust and impurities. In a cleanroom, use a gravity spray gun to evenly spray conductive coating onto the surface of the aircraft fairing. Then, use a stepped temperature curing method. Stage 1: room temperature → 120℃, heating rate 2℃ / min, and heat preservation for 1 hour. Phase 2: 120℃→200℃, heating rate 2℃ / min, holding for 1h; Phase 3: 200℃→500℃, heating rate 5℃ / min, holding for 2h; complete one conductive coating application, repeat three times to obtain a conductive coating on the surface of the aircraft fairing.
[0036] Example 3: A specific method for preparing a conductive coating on the surface of an aircraft fairing, comprising the following steps: S1. Add 1.1 kg of conductive phthalonitrile prepared according to Preparation Example 3 to 3 kg of N,N-dimethylformamide, stir at room temperature for 60 min, then add 50 g of dispersant BYK-110, 20 g of 3-aminopropyltriethoxysilane, 20 g of leveling agent BYK-333, and 10 g of defoamer BYK-066N, and continue stirring under ultrasonication for 20 min. After passing through a 200-mesh filter, a conductive coating is obtained. S2. Polish the surface of the aircraft fairing to remove dust and impurities. In a cleanroom, use a gravity spray gun to evenly spray conductive coating onto the surface of the aircraft fairing. Then, use a stepped temperature curing method. Stage 1: room temperature → 120℃, heating rate 2℃ / min, and heat preservation for 1 hour. Phase 2: 120℃→200℃, heating rate 2℃ / min, holding for 1h; Phase 3: 200℃→500℃, heating rate 5℃ / min, holding for 2h; complete one conductive coating application, repeat three times to obtain a conductive coating on the surface of the aircraft fairing.
[0037] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that conductive phthalonitrile is replaced with phthalonitrile.
[0038] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the conductive phthalonitrile prepared according to Preparation Example 2 is replaced with the conductive phthalonitrile prepared according to Comparative Preparation Example 1.
[0039] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the conductive phthalonitrile prepared according to Preparation Example 2 is replaced with the conductive phthalonitrile prepared according to Comparative Preparation Example 2.
[0040] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the conductive phthalonitrile prepared according to Preparation Example 2 is replaced with the conductive phthalonitrile prepared according to Comparative Preparation Example 3.
[0041] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the temperature in stage three of step S2 is reduced from 200℃→500℃ to 200℃→300℃.
[0042] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the stepped temperature rise curing in step S2 is replaced with a one-step temperature rise curing, which is room temperature → 500℃, heating rate 5℃ / min, and holding for 4 hours.
[0043] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that the conductive coating in step S2 was applied three times, but only once.
[0044] Performance testing: 1. Conductivity Test: Referring to GB / T 1410-2006 "Test Methods for Volume Resistivity and Surface Resistivity of Solid Insulating Materials" and SJ / T 10694-2006 "General Specifications for Antistatic Testing of Electronic Product Manufacturing and Application Systems", coating samples (100mm × 100mm × actual coating thickness) prepared in Examples 1-3 and Comparative Examples 1-7 were taken and left to stand for 24 hours at 23℃ and 50%RH. The surface was wiped with ethanol to remove oil and dust, and then allowed to air dry. A four-probe resistivity tester (model ST2258C) was used. Before testing, a standard resistance sheet (resistance value 10) was used. 2 Ω·cm, 10 5 Ω·cm, 10 8 Calibration (Ω·cm), surface resistance test: Press the probe of the four-probe tester vertically onto the coating surface, apply a 100V DC voltage, and record the value after the reading stabilizes; Volume resistivity test: Use a three-electrode system (main electrode diameter 50mm, ring electrode inner diameter 52mm, outer diameter 72mm), clamp the sample between the electrodes, apply a 500V DC voltage, and measure the current value according to the formula ρ v =(π×D 2 Calculate the volume resistivity (ρ) using (×U) / (4×d×I). v (where is the volume resistivity, D is the diameter of the main electrode, U is the voltage, d is the coating thickness, and I is the current). The experimental results are shown in Table 1.
[0045] 2. Radar Transmission Performance Test: Referring to GB / T 5597-2007 "Test Method for Microwave Complex Dielectric Constant of Solid Dielectrics" and GJB 2038A-2011 "Test Method for Reflectivity of Radar Absorbing Materials", the coating samples of Examples 1-3 and Comparative Examples 1-7 were processed into standard discs of Φ180mm×2mm (dielectrically matched with the radome substrate, the substrate being quartz glass). The surface was ensured to be flat and free of cracks. The thickness was measured using a micrometer. A vector network analyzer (model Agilent N5249A) was used, with a test frequency range of 8-12GHz. The coaxial probe method was employed, with the probe perpendicularly attached to the sample surface. After calibration using calibration components (open circuit, short circuit, load), the dielectric constant range and dielectric loss range were recorded. The experimental results are shown in Table 2. A free-space test system was set up (the distance between the transmitting and receiving antennas was 1m, and the sample was placed in the middle). A continuous wave with a frequency of 10GHz was transmitted. The received power (P0) without the sample and the received power (P1) with the sample were recorded. The radar wave transmittance was calculated according to the formula T=(P1 / P0)×100%. The experimental results are shown in Table 1.
[0046] 3. Environmental tolerance test: Take samples (100mm×50mm) from Examples 1-3 and Comparative Examples 1-7 and place them in a high and low temperature test chamber (model GDJS-500). Set the cycle program to -60℃ for 2h → heat up to 150℃ (rate 5℃ / min) → heat up for 2h → cool down to -60℃, for a total of 50 cycles. After the cycle, take out the samples and let them stand in an environment of 23℃ for 2h. Test the surface resistance and calculate the resistance retention rate (resistance after cycle / resistance before cycle × 100%). At the same time, observe whether the coating cracks or peels off. Referring to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", samples from Examples 1-3 and Comparative Examples 1-7 were placed in a salt spray test chamber (model YWX / Q-150). A 5% NaCl solution (pH=6.5-7.2) was used, with a spray pressure of 0.1 MPa and a temperature of 35℃. The spray was carried out continuously for 1000 hours. After the test, the samples were taken out, rinsed with deionized water and dried. The appearance of rust spots and bubbles on the surface was observed, the surface resistance was tested, and the resistance retention rate was calculated. Referring to GB / T 9286-1998 "Cross-cut test for paint and varnish films", samples from Examples 1-3 and Comparative Examples 1-7 were used. A 10×10 grid (grid spacing 1 mm, depth to the substrate) was drawn on the coating surface using a cross-cut tester. Debris was removed with a soft brush. 3M 600 tape was tightly applied to the grid area, left to stand for 1 minute, and then quickly peeled off at a 45° angle. The peeling of the coating at the grid edge was observed and rated according to the standard (0 grade: no peeling; 5 grade: complete peeling). The experimental results are shown in Table 3.
[0047] 4. Coating physical property test: Take samples (50mm×50mm) from Examples 1-3 and Comparative Examples 1-7, dry them in an 80℃ vacuum drying oven for 4 hours, remove them and cool them to room temperature in a desiccator, weigh them (m1, accuracy 0.0001g), completely immerse the samples in deionized water, let them stand at room temperature for 24 hours, remove them and blot the surface moisture with filter paper, weigh them immediately (m2); calculate the water absorption rate according to the formula, W=(m2-m1) / m1×100%; A coating thickness gauge (model TT260, accuracy 0.1μm) was used to select 25 test points (5×5 grid, spacing 0mm) on the sample surface of Examples 1-3 and Comparative Examples 1-7. The thickness value of each point was recorded, and the average thickness (d_avg) and maximum deviation (|d_max-d_avg|, |d_min-d_avg|) were calculated. When the maximum deviation was ≤5μm, it was considered "uniform". The experimental results are shown in Table 4.
[0048] Table 1. Conductivity test results Table 2 Radar Transmission Performance Test Results Table 3 Environmental tolerance test results Table 4 Test results of physical properties of coating Performance Analysis: As can be seen from the experimental data in Tables 1-3, the conductive coatings on the aircraft fairing surface prepared by the present invention in Examples 1-3 can achieve a balance of multiple performances, including static dissipation, radar transparency, environmental tolerance, and physical density, fully meeting the service requirements of the fairing, and their overall performance is significantly better than that of the comparative examples. Among them, Example 2 has the best overall performance, with higher conductivity, better radar signal transmission, and stronger resistance to high and low temperature cycling and salt spray corrosion. At the same time, the coating has lower water absorption and better thickness uniformity. This is due to the fact that Example 2 uses conductive phthalonitrile with the most suitable reaction parameters in Example 2, and combines it with the optimal process combination of stepped temperature curing and three-stage spraying, achieving synergistic effect between molecular design and preparation process.
[0049] Example 2 exhibits the best conductivity, likely due to the synergistic effect of the conjugated basis of the phthalonitrile molecule and the carbonization enhancement. The conductive phthalonitrile used has a 4,4-dihydroxystilbene backbone, with a benzene ring -CH=CH-benzene ring structure, and the vinylidene sp... 2The hybrid carbon forms a continuous conjugated system with the π electrons of the two benzene rings, providing a basic channel for intramolecular charge migration. The thiophene-pyrrole dione unit connected by ether bonds further expands the delocalization range of the conjugated electrons. The cyano group of the terminal phthalonitrile undergoes a trimerization reaction in the early stage of curing, forming a rigid triazine ring crosslinking network, which fixes the molecular orientation and promotes the close π-π stacking of conjugated segments of adjacent molecules, thus building a bridge for charge transmolecular transport. When the curing temperature rises to 500℃, the coating undergoes partial carbonization. The resin molecular chains lose some O and N heteroatoms, and the original conjugated chains further condense to form graphite-like microcrystalline regions. The triazine ring crosslinking network transforms into a more stable carbon skeleton. The originally dispersed conjugated regions are connected by "carbon bridges" formed by carbonization, constructing a continuous low-resistance conductive network across the coating. The conductivity of each comparative example is significantly lower than that of Example 2. The core reason is the failure of the conductive network construction: Comparative Example 1 uses ordinary phthalonitrile instead, lacking the continuous conjugated skeleton constructed from 4,4-dihydroxystilbene. Relying solely on cyano crosslinking cannot form an effective charge transport channel, resulting in only scattered carbon particles after carbonization, leading to a sharp drop in conductivity. Comparative Example 2 uses 4,4-dihydroxybiphenyl instead of 4,4-dihydroxystilbene. Biphenyl lacks vinylidene bridging, and the conjugated system breaks into isolated benzene rings, preventing long-distance charge transport and reducing conductivity. The strength increased significantly; Comparative Example 3, due to the absence of 5-bromo-2-fluoro-aniline, had a disordered monomer synthesis path, poor conjugated chain segment stacking, uneven distribution of graphite microcrystals after carbonization, and discontinuous conductive network; Comparative Example 4 replaced 4-nitro-2-trifluoromethyl-phthalonitrile with 4-nitrophthalonitrile, and the missing trifluoromethyl group led to a slight increase in molecular polarity, a decrease in π-π packing density, and an increase in charge transport resistance; Comparative Example 5 lowered the curing temperature to 300℃, which did not reach the carbonization threshold and could not form graphite-like microcrystals, relying only on the weak conductivity of the conjugated chain itself, resulting in extremely low conductivity efficiency; Comparative Example 6 used a one-step heating curing method, which caused the solvent to rapidly boil and form micropores, breaking the conductive channels, and the carbon skeleton at the micropores was discontinuous, resulting in a decrease in both conductivity uniformity and efficiency; Comparative Example 7 only performed a single spraying, resulting in uneven coating thickness, broken conductive channels in thin areas, and unstable overall conductivity performance, which was lower than that of Example 2. Example 2 exhibits the best radar transparency. This is likely because the trifluoromethyl group in the 4-nitro-2-trifluoromethyl-phthalonitrile unit introduced at the end of the conductive phthalonitrile significantly reduces the total molecular dipole moment, suppresses the polarization effect of the coating in the applied radar signal electric field, and keeps the dielectric constant within a gradient range compatible with air and the radome substrate, greatly reducing signal reflection on the coating surface. Simultaneously, during the stepped heating and curing process, slow heating and segmented heat preservation prevent rapid boiling of the solvent from creating micropores. The leveling agent optimizes the coating smoothness, and the dense structure formed by three layers of spraying, combined with the low polarity of the molecular skeleton, keeps the dielectric loss at an extremely low level, preventing excessive attenuation of the radar signal during transmission within the coating. The radar transparency of all comparative examples is inferior to that of Example 2, essentially due to the disruption of the dielectric balance: Comparative Example 1 uses ordinary... By replacing phthalonitrile, the polarity regulation effect of trifluoromethyl is eliminated, resulting in a sharp increase in molecular polarity, a significant increase in dielectric constant, enhanced signal reflection, and a substantial decrease in transmittance. In Comparative Example 2, the dielectric loss slightly increased due to the breakage of the conjugated skeleton and uneven charge distribution. Although the retention of trifluoromethyl prevented significant fluctuations in the dielectric constant, the transmittance was still lower than that of Example 2. In Comparative Example 3, the incomplete conjugated system intensified molecular polarity fluctuations, leading to increased dielectric loss, increased signal attenuation, and decreased transmittance. In Comparative Example 4, the absence of trifluoromethyl resulted in an increased molecular dipole moment, significantly increasing the dielectric constant, enhanced signal reflection, and a substantial decrease in transmittance. In Comparative Example 6, the micropores formed by one-step heating and curing led to increased dielectric loss, signal scattering and attenuation at the micropores, and decreased transmittance. In Comparative Example 7, the uneven thickness caused by a single spraying resulted in local dielectric differences, inconsistent signal transmission paths, and a transmittance lower than that of Example 2. Example 2 exhibits the best environmental tolerance, likely because the triazine ring network formed by the phthalonitrile cyano trimer during curing possesses high bond energy and chemical stability, resisting thermal stress generated by high-altitude and low-temperature cycling and resistant to corrosion from salt spray, ozone, and other corrosive media. The 3-aminopropyltriethoxysilane coupling agent tightly binds to the shroud substrate via silicon-oxygen bonds, while the amino groups interact with the resin molecules, significantly enhancing the interfacial adhesion between the coating and the substrate, preventing coating peeling caused by high-speed airflow erosion or high-low temperature cycling stress. Furthermore, the dense, microporous, and crack-free structure constructed by stepped temperature curing and three-stage spraying not only blocks the penetration path of corrosive media into the coating interior and substrate interface but also ensures the continuity of the conductive network, achieving stable performance during long-term service. The environmental tolerance of all comparative examples is weaker than that of Example 2, primarily due to defects in the protective system: Comparative Example 1 uses ordinary phthalonitrile, resulting in low crosslinking density and poor molecular stability, weak interfacial adhesion, and susceptibility to rust spots and blistering after salt spray corrosion, and further deterioration after high-low temperature cycling. Microcracks appeared, and the degree of peeling increased. In Comparative Example 3, due to the incomplete conjugated system, the intermolecular forces were weakened, the interfacial adhesion decreased, and the edges were prone to peeling after high and low temperature cycling. The protective ability decreased after salt spray corrosion. In Comparative Example 6, the micropores formed by one-step heating and curing provided a penetration channel for the corrosive medium. After salt spray, the coating blistered and blistered in many places. After high and low temperature cycling, the micropores were prone to cracking, and the resistance retention rate decreased significantly. In Comparative Example 7, the coating of a single spray was relatively thin, the interfacial bonding area with the substrate was small, the adhesion decreased, and the stress of high and low temperature cycling easily led to interfacial cracking, resulting in a decrease in resistance retention rate. Although the other comparative examples (2, 4, 5) retained the protective basis due to the molecular structure or process, the conjugation integrity, polarity regulation, or structural density were not as good as those of Example 2, and there were still gaps in environmental tolerance. Example 2 exhibits the best physical properties, likely because the solvent evaporates slowly during the stepped heating and curing process through segmented heating and heat preservation, avoiding micropores or cracks caused by solvent boiling. At the same time, the resin gradually cross-links and cures, forming a dense coating that significantly reduces water absorption. The three-coat overlay process, through multiple thin coats and curing, compensates for the uneven thickness that may exist in a single coat. Combined with the leveling agent, it significantly improves the uniformity of the coating thickness, keeping the maximum thickness deviation at a low level. The physical properties of each comparative example are inferior to Example 2, the root cause being defects in density and uniformity due to the process or structure: Comparative Example 6 uses a one-step heating and curing process, resulting in rapid solvent evaporation and premature resin cross-linking, forming numerous micropores and significantly increasing water absorption. Simultaneously, the uneven distribution of micropores increases the thickness deviation. Comparative Example 7 only performs a single coat, resulting in a thinner coating thickness that is prone to localized missed areas or uneven thickness, significantly increasing the maximum thickness deviation and worsening uniformity. Comparative Example 1, due to the low cross-linking density of ordinary phthalonitrile, has a loose coating structure and a slightly higher water absorption rate than Example 2. Comparative Example 3, due to an incomplete conjugated system and decreased molecular packing density, has a slightly insufficient coating density and increased water absorption. Although other comparative examples partially guarantee the structural foundation due to raw materials or processes, their density and uniformity are still inferior to Example 2.
[0050] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A conductive coating on the surface of an aircraft fairing, characterized in that, The raw materials include the following parts by weight: conductive phthalonitrile: 90-110 parts, N,N-dimethylformamide: 180-300 parts, dispersant BYK-110: 2-5 parts, 3-aminopropyltriethoxysilane: 1-3 parts, leveling agent BYK-333: 0.5-2 parts, defoamer BYK-066N: 0.5-1 part; The preparation process of the conductive phthalonitrile includes the following steps: (1) Under nitrogen protection, 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione was added to anhydrous dichloromethane and cooled to -78°C. Boron tribromide was added dropwise, and the temperature was controlled not to exceed -70°C during the dropwise addition. After the dropwise addition was completed, the reaction was stirred at -78°C for 1 h. Then the temperature was naturally restored to room temperature and the reaction was continued for 6-10 h. Then deionized water was added to quench the excess boron tribromide. The mixture was separated, and the organic phase was washed with saturated sodium carbonate and then with deionized water. After drying with anhydrous sodium sulfate, the solvent was removed by vacuum concentration. The crude product was purified by silica gel column chromatography with gradient elution to obtain 1-hydroxythieno[3,4-c]pyrrole-4,6(5H)-dione. (2) Under nitrogen protection, 5-bromo-2-fluoro-aniline, 4,4-dihydroxystilbene and potassium carbonate were added to dimethyl sulfoxide. The mixture was stirred and heated to 150-170℃ for 6-10 h. After cooling to room temperature, the solid was precipitated in dilute hydrochloric acid solution, filtered, collected, and recrystallized with ethanol to obtain monomer A. (3) Under nitrogen protection, monomer A, 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, potassium carbonate and potassium iodide were added to anhydrous sulfolane, and the mixture was heated to 135-145℃ with stirring. The reaction was carried out for 6-8 hours. After cooling to room temperature, the precipitate was poured into dilute hydrochloric acid solution, and the precipitate was collected by filtration. After washing three times with ethanol, the precipitate was dried to obtain monomer B. (4) Under nitrogen protection, monomer B was added to anhydrous sulfolane and heated to 80-90℃ with stirring. 4-nitro-2-trifluoromethyl-phthalonitrile was added and reacted for 8-10 hours. After cooling to room temperature, the solid was precipitated in dilute hydrochloric acid solution, filtered, collected, washed three times with ethanol, and dried to obtain conductive phthalonitrile.
2. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (1), the molar ratio of 1-methoxythieno[3,4-c]pyrrole-4,6(5H)-dione and boron tribromide is 1:1-1.
5.
3. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (1), 1-methoxythiopheno[3,4-c]pyrrole-4,6(5H)-dione and anhydrous dichloromethane are in a weight ratio of 1:8-12.
4. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (1), gradient elution refers to the volume ratio of dichloromethane and methanol in the eluent at each step, which is successively from 1:0, 50:1, 20:1 to 10:
1.
5. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (2), the molar ratio of 5-bromo-2-fluoro-aniline, 4,4-dihydroxystilbene and potassium carbonate is 2-2.4:1:2-3, the weight ratio of 5-bromo-2-fluoro-aniline, dimethyl sulfoxide and dilute hydrochloric acid solution is 1:8-12:20-30, and the mass concentration of dilute hydrochloric acid solution is 10%.
6. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (3), monomer A, 1-hydroxythiopheno[3,4-c]pyrrole-4,6(5H)-dione, potassium carbonate and potassium iodide are in a molar ratio of 1:1-1.5:1.5-2:0.1-0.2, monomer A, anhydrous sulfolane and dilute hydrochloric acid solution are in a weight ratio of 1:8-12:20-30, and the mass concentration of dilute hydrochloric acid solution is 10%.
7. The conductive coating on the surface of the aircraft fairing according to claim 1, characterized in that, In (4), the molar ratio of monomer B and 4-nitro-2-trifluoromethyl-phthalonitrile is 1:2-2.4, the weight ratio of monomer B, anhydrous sulfolane and dilute hydrochloric acid solution is 1:8-12:20-30, and the mass concentration of dilute hydrochloric acid solution is 10%.
8. The method for preparing a conductive coating on the surface of an aircraft fairing according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Add conductive phthalonitrile to N,N-dimethylformamide and stir at room temperature for 30-60 min. Then add dispersant BYK-110, 3-aminopropyltriethoxysilane, leveling agent BYK-333, and defoamer BYK-066N. Continue stirring under ultrasonication for 10-20 min. After passing through a 200-mesh filter, the conductive coating is obtained. S2. Polish the surface of the aircraft fairing to remove dust and impurities. In a cleanroom, use a gravity spray gun to evenly spray conductive coating onto the surface of the aircraft fairing. Then, use stepped temperature rise to cure the coating and complete one application of conductive coating. Repeat this process three times to obtain a conductive coating on the surface of the aircraft fairing.
9. The method for preparing the conductive coating on the surface of the aircraft fairing according to claim 8, characterized in that, The step-heat curing process in S2 is as follows: Phase 1: Room temperature → 120℃, heating rate 2℃ / min, hold for 1 hour; Phase 2: 120℃→200℃, heating rate 2℃ / min, hold for 1 hour; Phase 3: 200℃→500℃, heating rate 5℃ / min, hold for 2 hours.